Science projects about electricity and magnets - Gardner, Robert, 1929-; Delisle, Stephen F. (Berkeley Heights, N.J. : Enslow, 1994)
Contains electricity and magnetism projects for science fairs or recreation using simple materials which may be around home or school.
"Updated with internet sites"--Cover.
Includes bibliographical references (p. 121) and index.
Booklist.
School Library Journal.
Wilson's Junior High School.
Young Adult
Keywords: Electricity -- Experiments -- Juvenile literature; Magnets -- Experiments -- Juvenile literature; Science projects -- Juvenile literature; Science -- Exhibitions -- Juvenile literature; Electricity -- Experiments; Experiments; Magnets -- Experiments; Science projects; Electricity -- Experiments; Magnets -- Experiments; Science projects; Science -- Experiments